Impact of Flow Bursts in the Auroral Zone on the Ionosphere and Thermosphere. Issue 12 (7th December 2019) - Deng, Yue; Heelis, Roderick; Lyons, Larry R.; Nishimura, Yukitoshi; Gabrielse, Christine
Abstract: High‐latitude ionospheric plasma flows often contain embedded localized velocity enhancements with associated plasma density structures. Localized strong flows are significant energy sources to the thermosphere that are not contained in present empirical models of plasma convection. In this study, Global Ionosphere‐Thermosphere model, a nonhydrostatic model with flexible resolution, has been utilized to evaluate the influence of such localized strong enhancements of forcing on the global dynamics of the upper atmosphere. Specifically, three idealized configurations of flow burst have been examined, one flow burst with the typical spatial scale seen in the auroral zone, two neighboring flow bursts with the same spatial scale, and one flow burst with doubled spatial scale. The comparison between the cases with and without the flow burst illustrates that one regular‐sized flow burst at midnight can cause the neutral density to increase by 5% and the horizontal wind to increase by ∼30 m/s at 300 km altitude. The associated enhancement in the electron precipitation can increase total electron content by 15%( 1 TECU) during the first 15 min. Two simultaneous flow bursts can cause a rich wave structure with multiple wavelengths in traveling atmospheric disturbances due to wave‐wave interactions. A flow burst with doubled spatial size can increase the impact on the ionosphere/thermosphere by 2 times or even more. The outcome of this study illustrates substantial local and nonlocal responses of the ionosphere‐thermosphere system to the mesoscale energy and momentum inputs from the magnetosphere. Key Points: One regular‐sized flow burst at midnight can cause 5% neutral density increase and 30 m/s horizontal wind increase at 300 km altitude Two simultaneous flow bursts can cause a rich wave structure in traveling atmospheric disturbances (TADs) A flow burst with larger spatial size can very efficiently increase the impact on the ionosphere/thermosphere